Combining square-stepping exercise and strengthening exercise improve frailty status in pre-frail community-dwelling older adults - Ira Adventia; Lanny Indriastuti; Hari Peni Julianti (Indonesian Journal of Biomedicine and Clinical Sciences, 2025)
Frailty is a complex syndrome affecting older people, characterized by unintentional weight loss, low muscle strength, feelings of exhaustion, reduced physical activity capacity, and slow walking speed. A decrease of muscle strength has been shown to be a major cause of frailty. The studies further agreed that frailty is a treatable condition. Intervention at the pre-frail state may offer the best opportunity to prevent, delay, or reverse existing symptoms of physical frailty. The evidence that multicomponent exercise (particularly resistance exercise) can have marked effects on frailty and sarcopenia is now forceful. Thus, we combine strengthening exercise and square-stepping exercise (SSE), a popular balance exercise, in community-dwelling pre-frail older adults. To evaluate the effectiveness of additional lower extremity strengthening exercise on frailty phenotype scores in pre-frail older adults who receive SSE. This study used an experimental, randomized control trial on pre-frail older adults aged between 60 and 70 yr. The participants were divided into 2 groups of 19 people each. The control group received SSE 3 x /wk, while the treatment group received SSE 3 x /wk plus lower extremity strengthening exercises 2 x /wk for 6 wk. The analysis of each group revealed an improvement in frailty phenotype scores in both the treatment and control groups. Ten participants (55.56%) in the control group experienced an improvement in the frailty phenotype status to robust (non-frail). Eleven participants (64.71%) in the treatment group experienced an improvement in frailty phenotype status to robust (non-frail). These findings suggest that SSE can improve frailty phenotype scores in pre-frail older adults, and that adding lower extremity strengthening exercises to SSE significantly improves frailty phenotype score compared to SSE alone.